2016
DOI: 10.1007/s00300-016-1990-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA extracted from faeces as a source of information about endemic reindeer from the High Arctic: detection of Shiga toxin genes and the analysis of reindeer male-specific DNA

Abstract: DNA extracted from faeces may be a valuable source of information about the animal itself, as well as its microflora. An isolated reindeer population from Svalbard (Rangifer tarandus platyrhynchus) was tested for the presence of Shiga toxin encoding genes in the collected faecal samples. Even though the reindeers were not interacting with any other ruminants, which are considered to be a major reservoir of Shiga toxin containing bacteria, the stx1 gene was detected in 9 out of 10 tested samples, and the stx2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, studies on Spitsbergen have shown no significant differences in the high taxonomic ranks of bacterial structure communities between areas intensively fertilized by the little auk colony, characterized by high levels of nutrients and organic matter biomasses, and the control area (Zielińska et al 2016c). In this case, different physicochemical features of the soil had no substantial impact on the general bacterial community structure, at least at higher taxonomic ranks.…”
Section: Soil Microbiologymentioning
confidence: 80%
See 2 more Smart Citations
“…Nonetheless, studies on Spitsbergen have shown no significant differences in the high taxonomic ranks of bacterial structure communities between areas intensively fertilized by the little auk colony, characterized by high levels of nutrients and organic matter biomasses, and the control area (Zielińska et al 2016c). In this case, different physicochemical features of the soil had no substantial impact on the general bacterial community structure, at least at higher taxonomic ranks.…”
Section: Soil Microbiologymentioning
confidence: 80%
“…The abundance of invertebrates, such as springtails (Collembola) or water bears (Tardigrada), that inhabit mosses, lichens, liverworts and soil, was found to be higher where soils had become ornithogenically enriched (Stempniewicz et al 2006, Zawierucha et al 2015, Zmudczyńska-Skarbek et al 2015. Also, numbers and biomasses of each microorganism taxon and the whole structure of microbial communities can fluctuate in different soil environments, as a result of the changing physicochemical features of the soil (Aislabie et al 2009, Grzesiak et al 2015, Zielińska et al 2016c).…”
Section: Ornithogenic Soils -A Specific Example Of the Arctic Environmentioning
confidence: 99%
See 1 more Smart Citation